Prevalence of the use of medications requiring renal adjustment in critical care units of a public hospital - Dandara BINDEMANN; Lorena FRANQUETO; Antonio Matoso MENDES; Inajara ROTTA (Revista Brasileira de Farmácia Hospitalar e Serviços de Saúde)
Objective: To evaluate, among the most prescribed medications in the Intensive Care Units (ICU) of a public teaching hospital, those that require dose adjustment according to renal function, and to present the role of the pharmacist in this care setting. Methods: A cross-sectional observational study was conducted, with data collected from medication prescriptions through reports generated by the institution’s Hospital Information System from 2015 to 2019. Step 1: Based on the list of all medications prescribed during this period in two ICUs of the institution, the prevalence of prescription was calculated. For the 100 most used medications, a search was conducted on the Uptodate platform regarding the need for dose adjustment based on renal function. The data were compiled into a Microsoft Excel spreadsheet. Step 2: The compiled data were presented to five clinical pharmacists from the institution, who assessed the severity and likelihood of occurrence of potential nonadjustment of doses for the 10 most prevalent medications that require it, using the Hazard Score Matrix. Results: Of the 100 most prevalent, a total of 34 medications were identified that require dose adjustment, with the most predominant classes being antimicrobials (41.2%), followed by those related to the cardiovascular system (20.6%) and the central nervous system (17.6%). The medications that scored highest when evaluated by the Hazard Score Matrix were morphine and regular insulin, followed by enoxaparin and potassium chloride. It was noted that dose adjustment is necessary not only to reduce adverse reactions or nephrotoxicity but also to ensure therapeutic effectiveness. Conclusion: This study emphasized the importance of adjusting medication doses in critically ill patients with renal dysfunction. Many frequently prescribed medications require dose modifications to ensure safety and effectiveness, particularly those classified as ‘high-alert’ due to their narrow therapeutic range. Collaboration between physicians and pharmacists is essential for minimizing risks in this context. Additionally, the use of risk analysis tools, such as HFMEA, facilitates the implementation of preventive interventions and dose adjustment protocols.